Are Oral Health Status and Care Associated with Anxiety and Depression? A Study of Portuguese Health Science Students - Pedro Marques-Vidal, PhD; Virginia Milagre, MD (Blackwell Synergy, 2006)
The relationship between oral health and anxiety/depression were assessed in a cross-sectional study conducted in 38% Portuguese students from the Health Sciences (age: 21 f 3 years, 75% women).